Slow-transit constipation with concurrent upper gastrointestinal dysmotility and its response to transcutaneous electrical stimulation - Yik, Yee Ian; Clarke, Melanie C. C.; Catto-Smith, Anthony G.; Robertson, Val J.; Sutcliffe, Jonathan R.; Chase, Janet W.; Gibb, Susan; Cain, Timothy M.; Cook, David J.; Tudball, Coral F.; Hutson, John M.; Southwell, Bridget R. (Springer Verlag, 2011)
Purpose: Transcutaneous electrical stimulation (TES) speeds up colonic transit in children with slow-transit constipation (STC). This study examined if concurrent upper gastrointestinal dysmotility (UGD) affected response to TES. Methods: Radio-nuclear transit studies (NTS) were performed before and after TES treatment of STC as part of a larger randomised controlled trial. UGD was defined as delayed gastric emptying and/or slow small bowel transit. Improvement was defined as increase of ≥1 Geometric Centre (median radiotracer position at each time [small bowel = 1, toilet = 6]). Results: Forty-six subjects completed the trial, 34 had NTS after stimulation (21 M, 8-17 years, mean 11.3 years; symptoms >9 years). Active stimulation increased transit in >50% versus only 25% with sham (p = 0.04). Seventeen children also had UGD. In children with STC and either normal upper GI motility (NUGM) and UGD, NTS improved slightly after 1 month (57 vs. 60%; p = 0.9) and more after 2 months (88 vs. 40%; p = 0.07). However, mean transit rate significantly increased with NUGM, but not UGD (5.0 ± 0.2: 3.6 ± 0.6, p < 0.01). Conclusion: Transcutaneous electrical stimulation was beneficial for STC, with response weakly associated with UGD. As measured by NTS, STC children with NUGM responded slightly more, but with significantly greater increased transit compared to those with UGD. Higher numbers are needed to determine if the difference is important. © 2011 Springer-Verlag.